Respuestas

2012-07-30T03:14:31+02:00

1) log   [9(x+1)^2] = 2

        9 

     9^2 = 9(x+1)^2

       9   =  (x+1)^2

       sqrt(9) = x+1

        ±3 = x+1

              x= 2          ó        x= -4

                                     ABSURDO!

 

       ==> x=2

 

2) [2^2+2+1]*2^x  = 7/2

          7 * 2^(x+1) = 7

               2^(x+1) = 1

                        x = -1

2012-07-30T03:53:18+02:00

 log  [9(x+1)^2] = 2

        9 

     9^2 = 9(x+1)^2

       9   =  (x+1)^2

       sqrt(9) = x+1

        ±3 = x+1

              x= 2          ó        x= -4

 

lo lamento pero el segundo no lo entendi :P